Internal combustion engines performance, fuel economy and emissions (Woodhead Pub., 2013)
This book presents the papers from the Internal Combustion Engines: Performance, fuel economy and emissions held in London, UK. This popular international conference from the Institution of Mechanical Engineers provides a forum for IC engine experts looking closely at developments for personal transport applications, though many of the drivers of change apply to light and heavy duty, on and off highway, transport and other sectors. These are exciting times to be working in the IC engine field. With the move towards downsizing, advances in FIE and alternative fuels, new engine architectures and the introduction of Euro 6 in 2014, there are plenty of challenges. The aim remains to reduce both CO2 emissions and the dependence on oil-derivate fossil fuels whilst meeting the future, more stringent constraints on gaseous and particulate material emissions as set by EU, North American and Japanese regulations. How will technology developments enhance performance and shape the next generation of designs? The book introduces compression and internal combustion engines’ applications, followed by chapters on the challenges faced by alternative fuels and fuel delivery. The remaining chapters explore current improvements in combustion, pollution prevention strategies and data comparisons.--Provided by publisher.